Factors that Affect Mental Health in Adolescents: A Literature Review - Sadya Bustomi; Prihayati; Yenny Puspitasari (KHD Production, 2024)
Adolescence is a critical period in individual development marked by various physical, emotional, and social changes. Mental health at this age is very important because it can affect development and quality of life in adulthood. This research aims to identify and analyze factors influencing adolescent mental health through a literature review. The method used in this literature review is literature analysis from several international databases such as Scopus, Science Direct, PubMed, and Google Scholar. The results of the literature review show that adolescent mental health is influenced by various factors, including individual, family, school environment, and social factors. Individual factors include genetics, personality, and traumatic experiences. Family factors include family dynamics, parental support, and economic conditions. School environmental factors include academic pressure, peer relationships, and teacher support. Meanwhile, social factors include social media, community environment, and access to mental health services. This literature review found that the interaction between these factors plays an important role in shaping adolescent mental health. Strong social support, a stable family environment, and access to adequate mental health services can contribute positively to adolescent mental health. Conversely, high academic pressure, experiences of bullying, and lack of social support may be significant risk factors.